312 PACE: PROFESSIONAL ADVANCEMENT FOR CLINICIAN-EDUCATORS. (1st January 2005) - Chauvin, S.; Yang, T.; Lopez, F.; Sanders, C.
Abstract : Purpose: This presentation summarizes the initial development, implementation, and evaluation of the Professional Advancement for Clinician Educators (PACE) as a demonstration model of department level faculty professional development of clinician-educators. The model includes an educational scholarship workshop series, Grand Rounds presentations and mini-retreats on teaching/medical education, a department-wide educational enhancement project, informal small group discussions (roundtables), and individualized consultation for teaching and educational scholarship. Faculty participation is completely voluntary. Methods: Evaluation of the workshop series used pre-post session questionnaires targeting self-reported knowledge and self-efficacy for content and skills reflected in workshop objectives. Open-ended items targeted interests and intentions (pre-session) and session satisfaction (post-session). Descriptive summary statistics, Cronbach's alpha (internal consistency reliability), and Wilcoxon's signed rank t-test, appropriate to each session data set, were used to examine workshop effectiveness. Evaluation of other PACE components used case study (qualitative) methods. Results: Participants completing both pre- and post- session questionnaires ranged from 53-100%. Cronbach's alpha coefficients ranged from r = .80-.99, with all but one coefficient above r = .90. Total questionnaire results revealed significant gains from pre- to post-workshop self-reports (range: p = .0001 to p = .0349). Analysis of item pre-post differences revealed highly significant gains (p < .0001) for a large majority of items. Content analysis of responses to open-ended items revealed specific knowledge/skills learning and the effectiveness of authentic applications and hands-on learning. Qualitative results revealed significant impact of Grand Rounds presentations, mini-retreats, and department-wide project for enhancing teaching/learning and assessment processes and promoting new educational and professional development opportunities for faculty, residents, fellows, and students. Conclusion: Many faculty members devote significant time to teaching and education, but few have formal preparation in the science and scholarship of teaching. PACE is an effective and cost-effective model for nurturing and recognizing faculty members' professional development and achievements as clinician-educators. Minimal finances are needed to support PACE, but visible enthusiasm and recognition by department leaders are critical. Faculty members at all career stages (junior, mid-career, senior) participated regularly. Results reveal early impact and are very encouraging.